Science Teachers' Perspectives about Climate Change - Dawson, Vaille (Australian Science Teachers Association, 2012)
Climate change and its effects are likely to present challenging problems for future generations of young people. It is important for Australian students to understand the mechanisms and consequences of climate change. If students are to develop a sophisticated understanding, then science teachers need to be well-informed about climate change science. In this pilot study, thirty-nine science teachers and 417 Year 9/10 students from thirteen Western Australian schools were surveyed about their views of the importance of climate change science. Teachers and students also responded to questions to ascertain their understanding of climate change science, the challenges and consequences of climate change. Preliminary findings indicate that most of these teachers have a sound understanding of climate change science, recognising the importance of the greenhouse effect for life and the relationship between greenhouse effect and temperature. However, a proportion of teachers do not teach any climate change science. In this paper, the findings from the teachers are reported along with implications for preservice and inservice teacher education and curriculum development.